Hubungan Status Gizi Dengan Konsentrasi Belajar Pada Atlet Renang FIKK UNM - M. Rachmat Kasmad (Journal Physical Health Recreation (JPHR), 2024)
This study aims to determine the relationship between nutritional status and learning concentration of FIKK UNM swimming athletes. The independent variables in this study are sleep patterns and nutritional status, while the dependent variable is study concentration. This research is a quantitative research with an observational analytical design. The population in this study were all athletes, while the sample consisted of 30 respondents. The sampling technique in this research is total sampling. The data collection technique used was to provide a questionnaire containing several questions to respondents. Data were analyzed using the chi square test with a significance value of ρ < 0.05. The research results showed that the Chi Square Test was obtained on the relationship between sleep patterns and concentration (p-value = 0.025), which shows that there is a relationship between sleep patterns and nutritional status and the learning concentration of FIKK UNM swimming athletes.